Dependency Networks for Density Estimation, Collaborative Filtering, and Data Visualization - Heckerman, David; Chickering, Max; Meek, Chris; Rounthwaite, Robert; Kadie, Carl (Proceedings of Sixteenth Conference on Uncertainty in Artificial Intelligence, ® Stanford, CA, 2000)
We describe a graphical model for probabilistic relationships - an alternative to the Bayesian network - called a dependency network. The graph of a dependency network, unlike a Bayesian network, is potentially cyclic. The probability component of a dependency network, like a Bayesian network, is a set of conditional distributions, one for each node given its parents. We identify several basic properties of this representation and describe a computationally efficient procedure for learning the graph and probability components from data. We describe the application of this representation to probabilistic inference, collaborative filtering (the task of predicting preferences), and the visualization of acausal predictive relationships.